Kajian Perawatan Pada Pintu Penumpang Kereta Light Rail Vehicle Dengan Metode Reliability Centered Maintenance (RCM) - Dimas Adi Perwira; Akbar Zulkarnain; Henry Widya Prasetya; Reka Patria Raflyliano (Syntax Idea)
LRT Jakarta is one of the transportation service providers in the rail sector in the Jakarta area. LRT Jakarta has 8 trainsets of trains. In 1 trainset, the train has 8 passenger doors which have two types, namely type A and B. Vibration on the train causes the door to decrease gradually. Damaging often occurs when the train is operating, such as system errors and system failures. This study has the purpose to know the maintenance actions of the passenger system with Reliability Centered Maintenanc (RCM) and to know the possible causes of failure and the effects of the passenger door system of LVR train. This research uses Reliability Centered Maintenance. where the analysis has been done in the form of analysis of data processing starting from the functional block diagram. the next is the determination of the system and functional failure, by looking for the value of the risk priority number and failure mode and effect analysis. After that, the logic tree analysis prioritizes each mode of damage and performs a review of the functions; the last one provides a proposed maintenance action policy. The results of the research can be carried out actions on the components of the LRV train passenger door system where 7 components can be carried out maintenance actions with condition directed conditions and 1 component is carried out time directed actions. furthermore, the results of this study also explain about the possible failures and consequences caused to each component that has been discussed.